Pemetaan Kajian Pendidikan Islam pada Sekolah Tinggi Agama Islam Negeri Samarinda - Ahmad Riyadi (FENOMENA, 2014)
This study tries to map the Islamic Education research based on the citation both to the literature and the authors cited and listed in the bibliography. The citation of the name of the author and the research title were ranked to see how many times they were cited. Bibliometric analysis is also used to see the expancement of science by looking up the year of a literature when it was cited in an article. The result of study shows that: 1) The top authors which are listed in the bibliography are Anas Sudjiono, Suharsimi Arikunto, Hadari Nawawi, Oemar Hamalik, and Wina Sanjaya. 2) The top literatures which are cited are Prosedur Penelitian suatu pendekatan praktek, Pengantar Statistik Pendidikan, Metode Penelitian kualitatif, Administrasi and Supervisi pendidikan. These books are the primary sources to statistical data process and research methodology; quantitative and qualitative research. The books of curriculum, psychology, and education evaluation are found many times in the list of bibliography. The books, such as education, educational philosophy, Arabic language, and English language, are also found. 3) The average literature which were cited in the sarjana’s thesis of Educational faculty in 2013 is 9,69 year.